Iodine-131 induces ferroptosis and synergizes with sulfasalazine in differentiated thyroid cancer cells via suppressing SLC7A11 - Ling, Li; Zhang, Jinhe; Zhang, Xiao; Wang, Peiqi; Ma, Mingjun; Yin, Bingling (Frontiers in Oncology, 2025)
Iodine-131 (131I) plays a key role in the treatment of differentiated thyroid cancer (DTC). Ferroptosis represents a form of regulated cell death that is distinct from necrosis and apoptosis, constituting a unique mode of programmed cell death. In this study, we aimed to ascertain the potential of 131I to trigger ferroptosis in DTC and to assess the synergistic therapeutic impact of combining 131I with sulfasalazine (SAS), a ferroptosis inducer, in the context of DTC. The FTC-133 and TPC-1 cell lines were employed to evaluate the impact of 131I and SAS on cellular functions. Ferrostatin-1 (Fer-1) reversed the cell viability and colony formation ability inhibited by 131I. 131I led to an elevation in the levels of malondialdehyde (MDA), reactive oxygen species (ROS), and lipid peroxidation. DTC cells exposed to 131I displayed characteristic ferroptotic ultrastructure, featuring shrunken mitochondria with increased membrane density. Concurrently, there was a reduction in the content of glutathione (GSH), as well as a downregulation of the expression levels of glutathione peroxidase 4 (GPX4) and solute carrier family 7 member 11 (SLC7A11) in the cells treated with 131I. The CI values for the combination of SAS and 131I in DTC cells were less than 1, demonstrating that SAS synergized with 131I. Moreover, the combination of SAS and 131I significantly increased the MDA levels and lipid peroxidation, decreased the GSH levels, and suppressed the expression of SLC7A11 and GPX4, while SLC7A11 knockdown significantly enhanced ferroptosis-related markers in DTC cells. Animal experiments demonstrated that SAS synergized with 131I resulted in notable decreases in tumor volume and weight. Furthermore, immunohistochemical analyses revealed that the combination of 131I and SAS significantly downregulated the expression of GPX4 and SLC7A11 in vivo. Taken together, our results suggest that 131I may induce lipid peroxidation and ferroptosis, and demonstrate the potential for a synergistic therapeutic effect when 131I is combined with SAS in the treatment of DTC.